- Thread starter
- #1

#### Joystar1977

##### Active member

- Jul 24, 2013

- 119

Is it correct to say that the equation with x-intercepts would look like this:

y = (x - 2) (x + 1)

How do you factor the y-intercept?

- Thread starter Joystar1977
- Start date

- Thread starter
- #1

- Jul 24, 2013

- 119

Is it correct to say that the equation with x-intercepts would look like this:

y = (x - 2) (x + 1)

How do you factor the y-intercept?

- Admin
- #2

You are definitely on the right track. I would use the form:

Is it correct to say that the equation with x-intercepts would look like this:

y = (x - 2) (x + 1)

How do you factor the y-intercept?

\(\displaystyle y=k(x-2)(x+1)\)

Now let $y=4$ and $x=0$ and solve for $k$.